Surgical Catheterization for Continuous Serratus Anterior Plane Block after Thoracoscopic Lobectomy: A Report of 3 Cases - Soo Jung Park; Hanna Jung; Saeyoung Kim; Deok Heon Lee (Journal of Chest Surgery, 2022)
Serratus anterior plane block (SAPB) has been used for perioperative pain control during video-assisted thoracoscopic surgery (VATS), and the effects of continuous SAPB have been studied. This procedure is usually performed by the anesthesiologist; however, it could be performed more simply and safely by the thoracic surgeon through the use of meticulous finger dissection to create a space in the deep serratus anterior plane during surgery. We describe 3 cases of surgical catheterization for continuous SAPB in patients with lung cancer during VATS lobectomy, in which postoperative pain was effectively reduced.